Production and welfare of sows and pigs in lactation - Mumm, Jared Michael (Kansas State University, 2021)
Welfare of pigs has become a larger issue in the United States in recent years. The evolution of production facilities and production schemes require investigation into the performance of sows and piglets. Especially given public perception and changing regulations regarding food production. The use of technology as a strategy to decrease preweaning mortality may have detrimental effects on the sows and should be explored. Fifty-six sows treated with wearable novel technology to reduce preweaning mortality showed more exaggerated behavioral response to a simulated piglet crushing event by jumping or rising to a standing position more than control sows (P < 0.01). Sows treated with novel technology did not, however, show any greater physiological response to treatment than control sows (P > 0.10). Piglet birth order and management status (transferred or not) as well as sow treatment in lactation impact future piglet performance and welfare. The application of aversive stimuli to sows disrupted nursing stability. More piglets in VIB+EI treatment missed nursing bouts over the course of treatment (P=0.001). Birth order was grouped into categories (piglets born 1-5, 6-11, 12-18, 19-21) and transferred piglets. Earlier born piglets had a shorter latency to suckle (P = 0.05). Piglets that were transferred were more likely to move toward the sows head to suckle (P = 0.09). Transfer piglets and piglets in birth category three were less consistently in the same teat quadrant (P = 0.05) compared to earlier or late born piglets. Piglet weight was taken at birth, day seven and weaning. Transfer piglets were largest throughout, and latest born piglets gained a higher percentage of body weight over the course of lactation (P < 0.05). Multiple technological advances have been developed to both mitigate the loss of piglets around parturition, as well as increase their, and the sows welfare. The varying designs and results of which consistently indicate mortality risk is greater within early life and restricting sow movement is a common theme to prevent loss. Technology, and its impact on pork production is an evolving relationship. The use of novel technology can positively impact production numbers without impacting the overall welfare of the sows or piglets.
Keywords: Swine; Lactation; Behavior; Welfare; Technology